1998
DOI: 10.1136/vr.143.16.447
|View full text |Cite
|
Sign up to set email alerts
|

Rhizomucor pusillus mucormycosis combined with chlamydiosis in an African grey parrot (Psittacus erithacus erithacus)

Abstract: This paper describes a case of mucormycosis combined with chlamydiosis in an African grey parrot (Psittacus erithacus erithacus). The clinical signs included diarrhoea, an unsteady gait and a twisted neck. Smears of the spleen, liver and contents of the cloaca stained strongly positive for Chlamydia species. Histologically, hyphae typical of Zygomycetes were observed invading through the walls of blood vessels of the spleen. Rhizomucor pusillus was isolated as a pure culture from the intestines, lungs and live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…infection and one of only a few cases in parrots of alimentary tract zygomycosis confirmed by cytological and histological examinations, fungal culture and identification. 18 Gastrointestinal zygomycosis caused by R. microsporus var. rhizopodiformis has been described in humans in association with gastric carcinoma 19 and chronic granulomatous disease, 20 and in a pig with porcine circovirus infection.…”
Section: Discussionmentioning
confidence: 99%
“…infection and one of only a few cases in parrots of alimentary tract zygomycosis confirmed by cytological and histological examinations, fungal culture and identification. 18 Gastrointestinal zygomycosis caused by R. microsporus var. rhizopodiformis has been described in humans in association with gastric carcinoma 19 and chronic granulomatous disease, 20 and in a pig with porcine circovirus infection.…”
Section: Discussionmentioning
confidence: 99%
“…4,14 Mucormycosis is considered an uncommon mycotic disease of birds and generally is associated with gastrointestinal disease, although renal and respiratory disease have been reported. 2,3,[9][10][11] With the wide variety of clinical presentations that can be seen with fungal infections, mycotic disease should be considered for patients with a variety of clinical signs.…”
Section: Brief Communicationmentioning
confidence: 99%
“…are the most common cause of mycosis in birds, accounting for many cases of respiratory infections [ 1 , 13 ]. There are also a few reports of candidiasis or mucormycosis in chickens, ostriches, ducks and parrots, affecting the lungs, air sacs, liver, spleen and skeletal muscle [ 4 , 6 , 8 , 9 , 10 ]. In penguins, several cases of aspergillosis have been reported [ 5 , 15 ].…”
mentioning
confidence: 99%
“…Narrow hyphae with short irregular branching were 1 to 3 µ m in width and reacted positively to Fungiflora Y staining, which is a sensitive method to detect the cell wall components of most fungi, except for those of Mucoraceae. Although the possibility of mixed infection of fungi was suspected, because some case reports of mycosis indicated mixed infection with other fungi or bacteria [ 4 , 10 , 11 ], immunohistochemical examination revealed that all the fungi, excluding the rarely seen aspergilla, were Mucoraceae. The degeneration of fungi resulting from caseous necrosis may lead to an ambiguous reaction, as most of the narrow hyphae that exhibited positive reactions with Fungiflora Y were observed in or around the areas of necrosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation